Primary mediastinal B-cell lymphoma – metabolic and anatomical features in 18FDG-PET/CT and response to therapy - Kocurek, Anna; Małkowski, Bogdan; Giza, Agnieszka; Jurczak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Determining the role of PET/CT imaging in the evaluation of treatment efficacy in primary mediastinal B-cell lymphoma (PMBCL). Material and methods : Retrospective analysis of seven PMBCL patients, treated at the University Hospital in Krakow, with interim PET/CT after the third course of chemo-immunotherapy. The analysis was based on the calculation of exact tumour volume and metabolic activity, compared with initial values (directly after diagnosis). Results: Patients (five females, two males, average age 26.2 years, range 18–40 years), in clinical stage IIBX at diagnosis, were treated with eight cycles of R-CHOP-14 regimen, with radiotherapy consolidation (7/7) and central nervous system prophylaxis (6/7). The observed decrease in tumour volume between the initial staging and the interim PET ranged 72–89%. The mean ∆SUV max reduction between initial (when available) and interim PET was 87% (range 84–89%). In 3/7 cases in the interim PET/CT, the uptake of the tumour was higher than the liver (Deauville Criteria score 4–5), and in 4/7 it was lower than the liver but higher than mediastinal blood pool structures (score 3 according to Deauville Criteria). After a median follow-up of 58 months – OS and EFS is 100%. Conclusions: The excellent clinical outcome in the study group corresponds with very good metabolic and volumetric response in the interim PET. The ∆SUV max seems to be easier in implementation and has a more significant impact than other measurements.